Some properties of 2-absorbing primary ideals in lattices - Meenakshi P. Wasadikar; Karuna T. Gaikwad (AKCE International Journal of Graphs and Combinatorics, 2019)
We introduce the concepts of a primary and a 2-absorbing primary ideal and the radical of an ideal in a lattice. We study some properties of these ideals. A characterization for the radical of an ideal to be a primary ideal is given. Also a characterization for an ideal to be a 2-absorbing primary ideal is proved. Examples and counter examples are given wherever necessary.